Electrochemical studies of the ligand 1-hydroxyl-3-aminopropilydenephosphonic acid (APD) towards bone cancer therapy - Bilewicz, R. (University of Pretoria, 2013)
Dissertation (MSc (Chemistry))--University of Pretoria, 2006.